1992
DOI: 10.1007/bf01542269
|View full text |Cite
|
Sign up to set email alerts
|

Partnership after induced abortion: A prospective controlled study

Abstract: To study the social and psychological consequences of induced abortion on the relationship between the pregnant woman and her partner, 92 patients seeking a socially indicated abortion, who had a stable partner at the time of abortion, were interviewed. Standardized psychological measures were used to assess their partnerships before abortion and on follow-up 1 year later. A control group of 92 patients (matched for age, marital status, duration of partnership, number of children, and educational background), … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
21
0

Year Published

1997
1997
2014
2014

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 24 publications
(25 citation statements)
references
References 8 publications
4
21
0
Order By: Relevance
“…Sexual dysfunction after voluntary TOP has been already studied in literature [10–18]; however, to the best of our knowledge, this is the first study evaluating changes in sexual function after TOP by using a validated questionnaire and comparing two different procedures (medical vs. surgical). Our results demonstrate, for the first time, that the global assessment of female sexuality with the FSFI questionnaire, the number of sexual intercourses, and the self‐reported quality of sexual life are decreased in women undergoing first trimester surgical TOP compared with medical TOP at 1, 3, and 6 months follow‐up.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Sexual dysfunction after voluntary TOP has been already studied in literature [10–18]; however, to the best of our knowledge, this is the first study evaluating changes in sexual function after TOP by using a validated questionnaire and comparing two different procedures (medical vs. surgical). Our results demonstrate, for the first time, that the global assessment of female sexuality with the FSFI questionnaire, the number of sexual intercourses, and the self‐reported quality of sexual life are decreased in women undergoing first trimester surgical TOP compared with medical TOP at 1, 3, and 6 months follow‐up.…”
Section: Discussionmentioning
confidence: 99%
“…Old cohort studied showed that a percentage of women by around 10–20% report negative effects on sexual relationships in the first weeks and months following abortion, with a similar proportion of women also reporting problems over the first year (around 5–38%) [10–15]. Most of these studies focused on the relationship changes after TOP and/or inherited sexual dysfunctions; however, they present clear methodological problems (small sample size, not fixed timetable follow‐up, not homogenous cohort, and not validated and reproducible questionnaire used) [16–18].…”
Section: Introductionmentioning
confidence: 99%
“…For example, several studies have revealed an association between abortion and sexual dysfunction (Bianchi-Demicheli et al 2001;Rue et al 2004), communication problems (Freeman 1980), and separation or divorce (Barnett et al 1992;Bracken and Kasi 1975;Freeman 1980;Rue et al 2004). Although very few studies have examined abortion as a risk factor for domestic violence, one recent study did find an association between a prior history of abortion and violence during pregnancy (Hedin and Janson 2000).…”
Section: Abortion and Relationship Difficulties/ Partner-inflicted VImentioning
confidence: 95%
“…There are clinical reports linking sexual problems to abortion (Brien & Fairbairn, 1996) but few empirical studies. Those carried out suggest that some women experience some sexual problems or deterioration in sexual fulfilment shortly before and up to 6 months after their abortion, although for many other women there is either no change or an increase in satisfaction (Greer et al, 1976;Ashton, 1980;Barnett et al, 1992;Miller, 1992;Schleiss et al, 1997;Miller et al, 1998;Bianchi-Demicheli et al, 2002). The only study looking at this time period to include a comparison group found no differences in the quality of relationships (which included sexual relationships) of women due to have an abortion, compared to pregnant women (Tornbom et al, 1996).…”
Section: Introductionmentioning
confidence: 95%
“…A study by Barnett et al (1992) deserves more thorough discussion, as sexuality was studied prospectively and included a matched control group of non-pregnant women. Ninety-two West German women were interviewed a few days before and a year following abortion.…”
Section: Introductionmentioning
confidence: 99%